Bioimaging of microRNA124a‐independent neuronal differentiation of human G2 neural stem cells. Issue 1 (8th August 2015) - Lee, Jonghwan; Hwang, Do Won; Kim, Seung U.; Lee, Dong Soo; Lee, Yong Seung; Heo, Hyejung; Ali, Bahy A.; Al-Khedhairy, Abdulaziz A.; Kim, Soonhag
Abstract : Evaluation of the function of microRNAs (miRNAs or miRs) through miRNA expression profiles during neuronal differentiation plays a critical role not only in identifying unique miRNAs relevant to cellular development but also in understanding regulatory functions of the cell‐specific miRNAs in living organisms. Here, we examined the microarray‐based miRNA expression profiles of G2 cells (recently developed human neural stem cells) and monitored the expression pattern of known neuron‐specific miR‐9 and miR‐124a during neuronal differentiation of G2 cells in vitro and in vivo . Of 500 miRNAs analyzed by microarray of G2 cells, the expression of 90 miRNAs was significantly increased during doxycycline‐dependent neuronal differentiation of G2 cells and about 60 miRNAs showed a gradual enhancement of gene expression as neuronal differentiation progressed. Real‐time PCR showed that expression of endogenous mature miR‐9 was continuously and gradually increased in a pattern dependent on the period of neuronal differentiation of G2 cells while the increased expression of neuron‐specific mature miR‐124a was barely observed during neurogenesis. Our recently developed miRNA reporter imaging vectors (CMV/Gluc/3×PT_miR‐9 and CMV/Gluc/3×PT_miR‐124a) containing Gaussia luciferase, CMV promoter and three copies of complementary nucleotides of each corresponding miRNA showed that luciferase activity from CMV/Gluc/3×PT_miR‐9 was gradually decreased both in vitro and in vivo in G2 cells induced to differentiate into neurons. However, in vitro and in vivo bioluminescence signals for CMV/Gluc/3×PT_miR‐124a were not significantly different between undifferentiated and differentiated G2 cells. Our results demonstrate that biogenesis of neuron‐specific miR‐124a is not necessary for doxycycline‐dependent neurogenesis of G2 cells. Abstract : A bioinformatics approach was used to analyze neuron‐specific miRNA expression. A noninvasive luciferase imaging tool was used to confirm the miRNA expression profile. An integrated research strategy provided complementary information of better reliability. This strategy will be useful for study of miRNAs associated with differentiation and diseases.